The Bonding Interface and Tribological Properties of Cu–Graphite Sandwich Composites Fabricated via Accumulative Roll-Bonding Processes - Liu, Jinping; Ding, Yi; Sun, Ke; Zeng, Longfei; Xiao, Xiangpeng; Cao, Wei; Guan, Lijun; Ran, Jingyou; Sun, Zhe; Shi, Shuaifei; Zhang, Jianbo (Frontiers in Materials, 2022)
Copper-graphite sandwich composites is a new functional composites with excellent tribological and mechanical properties. More and more researchers prepare the sandwich composites by accumulative roll-bonding processes due to severe plasticity deformation. The microstructure and properties of copper-graphite sandwich composites prepared by continual annealing and accumulative roll-bonding processes for 8 rolling cycles were investigated. The results showed that, with the increase of rolling cycles, the dispersion of graphite particles between two copper layers along rolling direction became more uniform, the pores at the interface between graphite particles and Cu matrix gradually disappeared, and the hardness of copper-graphite composites gradually increased. After eight rolling cycles, the Vickers hardness of the composites increased by 140.8% as compared with that of annealed pure copper. During friction, the steel balls can meet some graphite particles in the composites rolled by four cycles. The friction coefficient and wear loss of copper-graphite composites gradually decreased with the increase of rolling cycles. Compared with the composites rolled by one cycle, the friction coefficient and wear loss of the composites rolled by eight cycles were reduced by 32.5% and 49.0%, respectively. The main wear mechanism gradually evolved from fatigue wear and abrasive wear to adhesive wear, and then to fatigue wear.